Knowledge and attitudes of mexican dentists regarding COVID-19 = Conocimiento y actitudes de dentistas mexicanos sobrela COVID-19 - Bermeo Escalona, Josué Roberto
Dentists have a high risk of contracting COVID-19, they needed to be aware of the major challenge that represents the dental practice and COVID-19. Accordingly, this study aimed: 1) to investigate the knowledge of dentists regarding COVID-19, 2) to investigate the attitudes of dentists concerning the use of personal protective equipment and, 3) to investigate the attitudes of dentists on stopping their dental practices in the framework of a contingency plan for the COVID-19 outbreak. An online cross-sectional survey was applied to dentists (n=822). Dentists in Mexico answered the survey, which was administered before the contingency plan for the COVID-19 outbreak. Results were analyzed with descriptive statistics and with a Chi-square test (P≤0.05). Of the respondents, 99% of dentists indicated knowing what COVID-19 is, knowing most, but not all, of its signs and symptoms and knowing its mode of transmission. The 89% of dentists indicated that they always used personal protective equipment. But they did not use always wear face masks, protective eyewear, face shields, disposable gowns, and caps. Dentists were aware of the risk of performing dental procedures during the COVID-19 outbreak. The 90% of dentists indicated that they would treat only patients requiring emergency treatment, and 10% indicated that they would not treat any patients. The dentists had limited knowledge about the COVID-19 disease. They did not use personal protective equipment consistently, and they indicated that they might continue working during the COVID-19 outbreak.